AS THE AGRICULTURE, FORESTRY AND FISHERIES SECTOR STILL AS A POTENTIAL IN THE PROSPERITY OF INDONESIAN SOCIETY? - Nugrahini Susantinah Wisnujati; Markus Patiung (Socio-Economics/Agribusiness Department, 2020)
All countries on the planet possibly be overseen ideally with the goal that their kin are prosperous. The Indonesian country has the potential for normal assets (ranger service, ranches, domesticated animals, fisheries and food crops) which in the Gross Provincial Homegrown Item (PDRB) are contracted as horticulture, ranger service and fisheries. The capability of the Indonesian country has endured a ton of harm and capacity changes. The exploration goals are (1) to investigate the horticultural, ranger service and fisheries parts as manageable areas or not, which add to the Gross Provincial Homegrown Item, (2) to dissect whether the farming, ranger service and fisheries divisions can succeed the Indonesian public. The explanatory strategies utilized are Area Remainder (LQ), Dynamic Area Remainder (DLQ) and Klassen Typology. The exploration results show that the horticultural, ranger service and fisheries divisions are essential/potential segments today and later on, although despite the fact their development is moderate and won't be supplanted by different segments until the apocalypse because of God's effortlessness. Just by dealing with its latent capacity, in particular horticulture, ranger service and fisheries, the Indonesian country can thrive its kin, with a note that it is important to join agribusiness and innovation, for example, GIS innovation, nano innovation that utilizes crude materials from farming, ranger service and fisheries.